2016
DOI: 10.5307/jbe.2016.41.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moisture Content and Seed Dimensions on Mechanical Oil Expression from African Oil Bean (Pentaclethra macrophylla Benth) Seed

Abstract: Purpose: New low-cost oilseeds are needed to meet an ever-increasing demand for oil for food, pharmaceutical, and industrial applications. African oil bean seed is a tropical crop that is underutilized and has high oil yields, but there have been no studies conducted on its mechanical oil expression up to now. The objective of this work was to investigate the effect of moisture content and seed dimensions on mechanical oil expression from the seeds. Methods: Fresh oil bean seeds were procured, de-hulled, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Oils can be obtained from seeds chemically using solvents or mechanically using set of devices like hydraulic press and oil expellers. Solvent extraction method is very efficient; it extracts approximately 98% oil though with the disadvantage of sophisticated equipment, high cost of investment, and technical expertise (Aremu & Ogunlade, , ; Aremu, Ibrahim, & Bamidele, ; Bargale, ; Bargale, Wulsfohn, Irudayaraj, Ford, & Sosulski, ; Bargale et al, ; Ibrahim & Onwualu, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oils can be obtained from seeds chemically using solvents or mechanically using set of devices like hydraulic press and oil expellers. Solvent extraction method is very efficient; it extracts approximately 98% oil though with the disadvantage of sophisticated equipment, high cost of investment, and technical expertise (Aremu & Ogunlade, , ; Aremu, Ibrahim, & Bamidele, ; Bargale, ; Bargale, Wulsfohn, Irudayaraj, Ford, & Sosulski, ; Bargale et al, ; Ibrahim & Onwualu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Independent variables that influence the quality and quantity of vegetable oil expressed mechanically include processing parameters like heat applications (duration and temperature) (Aktas, Gerçekaslan, & Uzlaşır, ; Raba, Chambre, Copolovici, Moldovan, & Copolovici, ; Rahma, Zekhnini, El‐Alem, & Hatimi, ) and moisture content (Fakayode & Ajav, ; Pornpipat, Hattha, & Tantanawat, ; Sarah, Widyastuti, & Ningsih, ; Udoh, Olayanju, Dairo, & Alonge, ; Zheng et al , ). Literature is very scanty on the effect of variables affecting the quality (yield) and quantity (characteristics) of vegetable oil expressed mechanically from African oil bean kernels (Aremu & Ogunalde, , ). Thus, this study aims to summarize the physical characteristics of vegetable oil as affected by processing conditions when expressed mechanically from African oil bean kernels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, [36] found the angle of repose and friction coefficient to be 17.20 o and 0.31, respectively. In their own work, [3] investigated the mechanical properties of the seed at moisture content range of 15.76 to 34.43% wet basis and loading rate of 25 mm/min., and they found the values of rupture force, toughness, rupture stress, yield force and modulus of stiffness of the seeds to decreased linearly from 362.04 to 168.82 N, 1.783 to 0.623 J, 7.4 to 3.15 N/mm 2 , 213.42 to 89.68 N and 39.6 to 21.97 N with moisture increase in transverse axis. Whereas for longitudinal loading, the values decreased from 276.64 to 195.26 N, 1.355 to 0.641 J, 16.12 to 6.23 N/mm 2 , 211.58 to 124.72 N and 38.74 to 24.77 N with an increase in moisture content.…”
Section: Engineering Properties Of African Oil Bean Seedsmentioning
confidence: 99%
“…Whereas for longitudinal loading, the values decreased from 276.64 to 195.26 N, 1.355 to 0.641 J, 16.12 to 6.23 N/mm 2 , 211.58 to 124.72 N and 38.74 to 24.77 N with an increase in moisture content. The seeds' physical and mechanical properties were affected by moisture content [3,35]. However, it was observed that adequate work had not been done on the thermal properties of the seeds despite the fact that heat treatment is essential for its processing.…”
Section: Engineering Properties Of African Oil Bean Seedsmentioning
confidence: 99%
“…The treated kernels were covered in closed polythene packs and stored under cold conditions for 2 days to promote uniform mix of moisture. Kernels were roasted in heating segment of the oil expeller Ogunlade, 2016a and2016b;Ogunlade and Aremu, 2019;2020) at different time and temperatures intervals (Table 1), oil samples obtained were untouched for 4 days prior to further experimentations (Weiss, 2000)…”
Section: Introductionmentioning
confidence: 99%